Family structure and expectations towards family roles in the opinion of Polish people - Chojnacka, Barbara; Iwański, Rafał (Wydawnictwo Naukowe EDUsfera, 2022)
The article presents the results of the analysis of the data illustrating the attitude of Poles towards two issues: the requirement of the completeness of the family as a condition for creating the most appropriate educational environment for a child, and traditional family roles, especially due to the tasks assigned to women and men. The most important socio-demographic variables were taken into account: age, sex, place of residence, level of education, which were important for differentiating the respondents’ opinions on the above-mentioned issues.
Keywords: family structure; family transformations; system of roles in the family